National Universities in Argentina during the pandemic outbreak - Mendonça, Mariana (2020)
The health emergency that Argentina is experiencing due to the COVID-19 pandemic radically changed institutional normality at all educational levels. Universities have certainly not escaped this logic. While their first response was a general shut down, along with a shift to online teaching and learning, the actions taken in response to the pandemic went far and beyond. In point of fact, these institutions sought to contribute, in different ways, to satisfy the new social demands linked to the outbreak of the health emergency. In this manuscript we propose to give an account of the actions that the national universities in Argentina took in response to the distinctive social demands linked to the pandemic outbreak. Specifically, we will focus on the academic and pedagogical decisions; the reorientation of scientific research; the availability of infrastructure and resources for the COVID-19 treatment; and the responses to the social demands of local communities. To this end, we will work with institutional documents from the national universities, the National Inter-University Council, the Ministry of Education and the Ministry of Science and Technology. We also used news sources, such as newspapers articles and the universities web sites.